Outcome of patients with nonmetastatic muscle‐invasive bladder cancer not undergoing cystectomy after treatment with noncisplatin‐based chemotherapy and/or radiotherapy: a retrospective analysis. (22nd March 2016) - Bamias, Aristotle; Tsantoulis, Petros; Zilli, Thomas; Papatsoris, Athanasios; Caparrotti, Francesca; Kyratsas, Christos; Tzannis, Kimon; Stravodimos, Kostas; Chrisofos, Michael; Wirth, Gregory J.; Skolarikos, Andreas; Mitropoulos, Dionysios; et al.
Abstract: Transurethral resection of bladder tumor (TURBT), radiotherapy, chemotherapy, or combinations can be used in patients with muscle‐invasive bladder cancer (MIBC) not undergoing cystectomy. Nevertheless, unfitness for cystectomy is frequently associated with unfitness for other therapeutic modalities. We report the outcome of patients with MIBC who did not undergo cystectomy and did not receive cisplatin‐based chemotherapy. Selection criteria for the study were nonmetastatic MIBC, no cystectomy, no cisplatin‐based chemotherapy. Chemotherapy and/or radiotherapy should have been used aside from TURBT. Forty‐nine patients (median age 79), managed between April 2001 and January 2012, were included in this analysis. Median Charlson Comorbidity Index was 5, while 76% were unfit for cisplatin. Treatment included radiotherapy ( n = 7), carboplatin‐based chemotherapy ( n = 25), carboplatin‐based chemotherapy followed by radiotherapy ( n = 10), and radiochemotherapy ( n = 7). Five‐year event‐free rate was 26% (standard error [SE] = 7) for overall survival, 23% (SE = 7) for progression‐free survival, and 30 (SE = 8) for cancer‐specific survival (CSS). Patients who were treated with combination of radiotherapy and chemotherapy had significantly longer CSS compared to those treated with radiotherapy or chemotherapy only (5‐year CSS rate: 16% [SE 8] vs. 63% [SE 15], P = 0.053). Unfit‐for‐cystectomy patients frequently receive suboptimal nonsurgical treatment. Their outcome was poor. Combining chemotherapy with radiotherapy produced better outcomes and should be prospectively evaluated. Abstract : We herein report the outcome of patients with muscle‐invasive bladder cancer who did not undergo cystectomy and did not receive cisplatin‐based chemotherapy as they were unfit for both treatment modalities. Treatment included transurethral resection of the tumor, radiotherapy, and carboplatin‐based chemotherapy. The outcome of these patients was poor, reflecting the limited therapeutic options and the lack of clinical research focused on this population.